Data analysis systems for sailing sports reserve training service - Bakulev, S. E.; Ashkinazi, S. M.; Kulikov, V. S.; Ryabchikov, V.V.; Tajmazov, V. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze benefits of the new experimental Fast Skipper Data Analysis Systems for application in the national sailing sports reserve training systems.